Completely‐in‐the‐Canal Magnet‐Drive Hearing Device: A Temporal Bone Study. Issue 3 (21st December 2012) - Mahboubi, Hossein; Malley, Melinda J. D.; Paulick, Peyton; Merlo, Mark W.; Bachman, Mark; Djalilian, Hamid R.
Abstract : The magnet‐drive hearing device (MHD) is a small completely‐in‐the‐canal hearing aid prototype that drives the tympanic membrane (TM) through a magnetic interface. A cadaveric temporal bone was prepared. The MHD was coupled to a nickel‐epoxy pellet glued to the umbo. Frequency sweeps between 0.3 and 10 kHz were performed, and the MHD was driven with various levels of current. Displacements of the posterior crus of the stapes were measured using a laser Doppler vibrometer and compared with sound‐induced displacements. The MHD had a linear frequency response and low total harmonic distortion. The pellet placement altered the stapes movements; however, the changes were statistically insignificant. Inputs of 100 and 300 mV produced displacements equivalent to those of the natural sound at 70‐ and 80‐dB sound pressure level, respectively. The coupling of this novel device using a magnetic interface to the umbo had a frequency output wider than air conduction devices, and its actuator was effective in driving the TM.